Construction of Pupil Identities at School - Grivins, Mikelis (Socialinė teorija, empirija, politika ir praktika, 2013)
SummarySeveral theorists who have analysed education on the micro-level have illustrated how mutual relations and process interpretation influence the education results. Furthermore, these authors show why relations are more beneficial to some pupils than to others. However, explanations why some pupils tend to benefit more are still simplistic, addressing only some of involved agents. This paper analyses how pupil identities in school are constructed. A teacher – one of the agents involved in the education process – holds the power to control the education process of pupils. Additionally, he has power to reinterpret the identities of other involved agents. However, although a teacher has power to state pupil connections to school, a pupil has power not to accept or follow the teacher’s definitions. In this paper, I show how these two agents interpret pupil’s identity and how differences in the interpretation occur. I approach identity construction at school from the perspective of three involved agents – pupils,teachers, and classmates. I analyse the text of 34 interviews with teachers and pupils. The analysis is structured so that it could represent three important agents that can influence identity construction, i. e. teachers, pupils, and classmates. I conclude that there are differences how pupil identity is influenced by the mentioned agents.Key words: school, identities, educationnbsp;